Species composition and distribution of dangerous scorpions of Hemiscorpius genus and clinical symptoms due to envenomation in high-risk regions of southern Iran - Mehran Shahi; Seyed Hamid Moosavy; Ahmad Ali Hanafi-Bojd; Morteza Akbari; Javad Rafinejad (Society for Indonesian Biodiversity, 2021)
Abstract. Shahi M, Moosavy SH, Hanafi-Bojd AA, Akbari M, Rafinejad J. 2021. Species composition and distribution of dangerous scorpions of Hemiscorpius genus and clinical symptoms due to envenomation in high-risk regions of southern Iran. Biodiversitas 22: 2945-2951. The southern regions of Iran, including Hormozgan province, are high risk areas for scorpion stings. This study aimed to determine the distribution and species diversity of dangerous scorpions of Hemiscorpius and also to determine the clinical symptoms of their bites in the high-risk areas of Hormozgan province. Scorpion sampling was carried out from Shahid Mohammadi and Koodakan hospitals in Bandar Abbas also filed areas of Bandar Abbas and Khamir counties by searching the scorpion's shelter throughout the day and using ultraviolet light at night. To determine the clinical symptoms, the data recorded in the patient's file were extracted and recorded in the sting checklists. Five species of the Hemiscorpius genus were identified. H. gaillardia and H. persicus are reported for the first time from Hormozgan province. Specific clinical symptoms after several hours of delayed were pain, swelling, itching, warmth, and edema, necrosis of the sting site, nausea, vomiting, dizziness, and fever. Complications such as urine discoloration, hemoglobinuria, severe hemolysis, and acute renal failure were observed. The results showed that envenomation with Hemiscorpius Scorpions should be considered as an urgent medical issue.